Salmen at sige Verden ret Farvel - belyst ved Grundtvigs samtidige prædikener - Holm, Jette (Grundtvig-Studier, 1997)
The Hymn To Say the World a Right Farewell - in the Light of Grundtvig 's Contemporary Sermons By Jette Holm Grundtvig wrote the hymn At sige verden ret farvel (To Say the World a Right Farewell) for himself. The first 5 stanzas and the final stanza were composed in Easter 1843 (2 drafts). Stanzas 6-8 were added around Advent 1844. In Easter 1843 Grundtvig felt immensely moved by the sound of His voice saying: I am the resurrection and the life: he that believeth in me, though he were dead, yet shall he live; And whosoeverr liveth and believeth in me shall never die (John 11). The sermon on Easter morning ends by quoting 2 stanzas and the final stanza of the hymn To say the World a Right Farewell. The version of these three stanzas varies slightly compared with Grundtvig’s hymn manuscript and has not previously been known to Grundtvig scholars. It is argued that Grundtvig probably composes the two new stanzas in connection with his sermons for Easter Sunday and Easter Monday, and these sermons help to throw light on the content of the hymn. In the spring of 1843 Grundtvig is preparing a hymn book supplement: Psalm-Leaves for Church-Use (or Unprinted Psalm Leaves) in reply to Mynster’s A Proposal for a Supplement to the Evangelical-Christian Hymn Book, 1843. The issue of the hymns takes a new turn when the Clerical Conference of Copenhagen sets up a committee in February-March 1844 with Grundtvig as a member. The task of the committee is to attempt to put together a new hymn book to replace the Evangelical-Christian Hymn Book. In the spring of 1844 Grundtvig is ill and in a deep crisis; but in the autumn of 1844 he begins work in the committee. When Mynster criticizes the work on a complete hymn book, Grundtvig decides to edit his Unprinted Psalm Leaves. The first two sheets of Printed Psalm Leaves have left the printers in November 1844, but the Hymn Committee persuades Grundtvig to have the supplement published as a specimen copy: Church Hymns Published on Trial by the Hymn Committee of the Clerical Conference of Copenhagen, January 1845. In the specimen copy the hymn To say the World a Right Farewell has 3 stanzas added to it. These stanzas reflect Grundtvig’s crisis in the spring of 1844. The content of the new or altered stanzas of the hymn is discussed and elucidated through Grundtvig’s contemporary sermons. In the autumn of 1844 Grundtvig often preaches about faith, hope and charity. As Christianity is always and everywhere three-fold, embracing faith, hope and charity, so is Grundtvig’s own hymn, too. With a certain caution it may be said that the three stages in the development of the hymn correspond to faith, hope and charity: the two first drafts corresponding to faith and hope, and the third in 1844 to charity.